The role of placental elastography in postpartum blood loss in multiparous pregnancies - Akay, Arife; Akdaş-Reis, Yıldız; Erbey, Sait; Tatar, Özde Beren; Diktaş, Elif Gülşah; Çukurova, Ece Sevin; Fıratlıgil, Fahri Burçin; Akpınar, Funda (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
The objective of this study was to assess the link between postpartum blood loss and placental elastography in multiparous pregnancies.In this prospective study, multiparous women who delivered at term between 2020 and 2024 were included. During the obstetric ultrasonography procedure, placental elastography was evaluated through the utilization of the shear wave elastography (SWE) technique. Elastographic measurements were performed at three distinct sites within the anteriorly positioned placentas via the abdominal route. The mean value of these three sites was subsequently calculated to derive the Z score. The difference (Δ) between prepartum and postpartum hemoglobin values was calculated, and cases with ΔHB below 2 g/dl were considered as the control group, and those with ΔHB above 2 g/dl were considered as the study group. Z scores were then compared between the two groups.A total of 109 cases was included in the study, 88 (80.7%) of which were assigned to the control group, and 21 (19.3%) to the study group. Maternal age (30.4±4.82 vs. 31.7±6.68) and BMI (28.7±3.96 vs. 28.1±4.77 kg/m2) were similar in both groups (p>0.05). A positive relationship was identified between ΔHB levels and Z score (r=0.521, p<0.001). The optimal cut-off value for the Z score was determined to be 5.64 kPa, exhibiting 76.2% sensitivity and 52.3% specificity (AUC: 0.709, p=0.003, 95% CI 0.586-0.833).The elastographic evaluation of the prepartum placenta has the potential to serve as a valuable tool in estimating postpartum hemoglobin decline.
Keywords: Birth; Blood Loss; Elastography; Hemoglobin; Placenta